EGFR inhibitors-related panniculitis: A new side effect - Sofia Lopes; Ana Nogueira; Joana Pardal; Filomena Azevedo (Wolters Kluwer Medknow Publications, 2019)
Epidermal growth factor receptor (EGFR) inhibitors are widely used in the treatment of advanced malignancies, and their skin toxicity is frequent and well recognized in the literature. We report the case of a 69-year-old patient with a history of adenocarcinoma of the lung treated with several EGFR inhibitors and the development of skin lesions compatible with panniculitis. The reproducibility of the lesions with different inhibitors reinforces the causal relationship with the drug, representing the first report in the literature of this side effect.